2019
DOI: 10.1021/acs.inorgchem.9b00270
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pb Filling and Synthesis Pressure Regulation on the Thermoelectric Properties of CoSb3

Abstract: To take the advantage of the synergy of atom filling and pressure regulation, atom Pb was assumed to play the role of fillers to occupy the Sb-icosahedron voids. In this paper, skutterudite Pb x Co4Sb11.5Te0.5 materials have been synthesized by high-pressure and high-temperature (HPHT) method with 0.5 h processing time. Although the increase of Pb filling rate increased the electrical resistivity of samples, it reduced the thermal conductivity of samples significantly. When the synthesis pressure increased, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…In addition, some special structures (such as in situ nanostructures [158], dislocation arrays [159,160], nanocrystalline polymer, and lattice distortion [161]) can also be introduced into the CoSb 3 -based materials by the microstructure and composition engineering [158,162], dislocation engineering [159] or grain boundary engineering [160], pressure regulation [161], and novel preparation methods [163][164][165]. The introduction of these special structures can also significantly improve the TE properties of CoSb 3 -based materials.…”
Section: Low Dimensionalmentioning
confidence: 99%
“…In addition, some special structures (such as in situ nanostructures [158], dislocation arrays [159,160], nanocrystalline polymer, and lattice distortion [161]) can also be introduced into the CoSb 3 -based materials by the microstructure and composition engineering [158,162], dislocation engineering [159] or grain boundary engineering [160], pressure regulation [161], and novel preparation methods [163][164][165]. The introduction of these special structures can also significantly improve the TE properties of CoSb 3 -based materials.…”
Section: Low Dimensionalmentioning
confidence: 99%
“…Such pressureinduced reduction in grain sizes is observed in various thermoelectric materials [116][117][118][119]. For instance, Deng et al reported that CoSb 3 -based alloys, as shown in figures 5(A) and (B) [120], were synthesized under different pressures (∼GPa), the observation found that the grain sizes exhibited a significant decrease with increasing pressure. The analogous situation occurs in the synthesis of polycrystalline SnSe as well [121], in contrast with the former, the magnitude of pressure is ∼MPa level applied in the preparation process of SnSe, which is far less than ∼GPa level.…”
Section: Microstructural Evolution With Pressurementioning
confidence: 79%
“…2(d)) with the increase in the Ni doping amount, which might be due to the modification in the crystal structure caused by Ni doping. In addition, the distortion caused by Ni doping may disturb the phonon propagation and reduce the thermal conductivity [38]. Therefore, the Raman scattering spectra also show that the Ni atoms were successfully doped into the p-type skutterudite at the Fe sites.…”
Section: Computational Detailsmentioning
confidence: 99%